Potential long‐term effect of tumor necrosis factor inhibitors on dementia risk: A propensity score matched retrospective cohort study in US veterans. Issue 6 (27th September 2021) - Zheng, Chunlei; Fillmore, Nathanael R.; Ramos‐Cejudo, Jaime; Brophy, Mary; Osorio, Ricardo; Gurney, Mark E.; Qiu, Wei Qiao; Au, Rhoda; Perry, George; Dubreuil, Maureen; Chen, Shu G; Qi, Xin; et al.
Abstract: Introduction: Tumor necrosis factor (TNF) inhibitors are widely used to treat rheumatoid arthritis (RA) and their potential to retard Alzheimer's disease (AD) progression has been reported. However, their long‐term effects on the dementia/AD risk remain unknown. Methods: A propensity scored matched retrospective cohort study was conducted among 40, 207 patients with RA within the US Veterans Affairs health‐care system from 2000 to 2020. Results: A total of 2510 patients with RA prescribed TNF inhibitors were 1:2 matched to control patients. TNF inhibitor use was associated with reduced dementia risk (hazard ratio [HR]: 0.64, 95% confidence interval [CI]: 0.52–0.80), which was consistent as the study period increased from 5 to 20 years after RA diagnosis. TNF inhibitor use also showed a long‐term effect in reducing the risk of AD (HR: 0.57, 95% CI: 0.39–0.83) during the 20 years of follow‐up. Conclusion: TNF inhibitor use is associated with lower long‐term risk of dementia/AD among US veterans with RA.